Wielopoziomowe modele strukturalne w badaniach marketingowych - porównawcza analiza więzi relacyjnych na rynku usług - Rudawska, Iga; Sagan, Adam (Multilevel Structural Models in Marketing Research - Comparative Analysis of Relational Bonds on the Service Market, 2006)
"The character of this paper is methodological. It is dedicated to the application of multilevel structural equation models in the marketing research. It is a relatively new approach in the marketing research, especially in comparative international and spatial studies, thus the authors describe essence and goals of the multilevel modeling. Next, the empirical example has been given and the multigroup - multilevel model of relational bonds in the healthcare market has been built. "
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 507-514